A Skeletal Kinetic Model For Biodiesel Fuels Surrogate Blend Under DieselEngine Condition - Chit Wityi Oo; Masahiro Shioji; Hiroshi Kawanabe; Susan A Roces; Nathaniel P Dugos (ASEAN Journal of Chemical Engineering, 2015)
The biodiesel surrogate fuels are realistic kinetic tools to study the combustion of actual biodiesel fuels in diesel engines. The knowledge of fuel chemistry aids in the development of combustion modeling. In order to numerically simulate the diesel combustion, it is necessary to construct a compact reaction model for describing the chemical reaction. This study developed a skeletal kinetic model of methyl decanoate (MD) and n-heptane as a biodiesel surrogate blend for the chemical combustion reactions. The skeletal kinetic model is simply composed of 45 chemical species and 74 reactions based on the full kinetic models which have been developed by Lawrance Livermore National Laboratory (LLNL) and Knowledge-basing Utilities for Complex Reaction Systems (KUCRS) under the diesel like engine conditions. The model in this study is generated by using CHEMKIN and then it is used to produce the ignition delay data and the related chemical species. The model predicted good reasonable agreement for the ignition delays and most of the reaction products at various conditions. The chemical species are well reproduced by this skeletal kinetic model while the good temperature dependency is found under constant pressure conditions 2MPa and 4MPa. The ignition delay time of present model is slightly shorter than the full kinetic model near negative temperature coefficient (NTC) regime. This skeletal model can provide the chemical kinetics to apply in the simulation codes for dieselengine combustion.